Regenerated graphite for lithium-ion batteries

JP7649364B2Active Publication Date: 2025-03-19ASCEND ELEMENTS +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2023207877
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2023-02-27
Filing Date
2023-12-08
Publication Date
2025-03-19
Estimated Expiration
2043-12-08

AI Technical Summary

Benefits of technology

【0003】 本明細書における構成は、電気及びハイブリッド自動車(EV及びHV)の人気の増大が、NMC(Ni、Mn、Co)カソード材料並びにグラファイト及び類似の炭素形態を含むアノード材料などの電荷材料を含む大量の使用済みリチウムイオン電池を生成するという観察に部分的に基づく。NMC電荷材料のための再生プロセスは、技術又は顧客仕様に従って電荷材料金属の所定の比率を実現するために、Ni、Mn、Co塩の対照(バージン)ストックを使用した増強を多くの場合に伴う、使用済みのNMC電荷材料の浸出を実行する。使用済みのリチウムイオン電池からグラファイトを回収することもできる。残念ながら、NMC再生に対する従来の方式には、回収されたグラファイトの粒子が、細断及び浸出プロセス後に残留物として残る、最も顕著には酸化アルミニウムである不純物を有するという欠点がある。大量の不純物が再生グラファイト製品中に留まる場合、性能及び物理的なアノード材料特性に関する顧客仕様を満たすことが問題となり得る。従って、本明細書における構成は、99.5%以上及び99.9%に近い改善された純度を有するグラファイトを含むアノード材料を生成することにより、従来の電池の再生の欠点を大幅に克服する。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007649364000001
    Figure 0007649364000001
  • Figure 0007649364000002
    Figure 0007649364000002
  • Figure 0007649364000003
    Figure 0007649364000003
Patent Text Reader

Abstract

To provide recycled graphite for Li-ion batteries.SOLUTION: A method of producing a purified graphite from a recycled battery stream for use as anode material in Li-ion batteries is described. The method comprises a leaching step to obtain a precipitate comprising graphite by filtration, the precipitate then being iteratively roasted as a slurry with an aqueous solution of a hydroxide base and subsequently washed to form a purified graphite.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Background technology]

[0001] background Lithium-ion batteries are the preferred chemistry for secondary (rechargeable) batteries in high-discharge applications such as electric vehicles (EVs) and power tools where rapid acceleration of electric motors is required. Lithium-ion batteries contain charge materials, conductive powders and binders applied or deposited on a current collector, usually a flat sheet of copper or aluminum. The charge materials contain an anode material, usually graphite or carbon, and a cathode material, which contains metals such as lithium, nickel, manganese, cobalt, aluminum, iron and phosphorus in predetermined ratios, thereby defining the so-called "battery chemistry" of the lithium-ion cell. The preferred battery chemistry varies between suppliers and applications, and lithium-ion battery regeneration efforts usually follow a specified molar ratio of battery chemistries in the regenerated charge material product. The purity of the constituent products is highly relevant to the quality and performance of the regenerated cell, which often depends on so-called "battery grade" materials, meaning 99.5% purity. Summary of the Invention [Means for solving the problem]

[0002] overview The purification process for regenerated graphite used as an anode material in lithium-ion batteries involves a sequence of roasting, followed by washing with deionized (DI) water, and optionally followed by acid washing. The graphite source is the result of a suitable process, such as acid leaching of black mass from a battery regeneration stream. Impurities, most notably aluminum oxide, are often present in trace amounts in the graphite source. The roasting process is repeated multiple times to purify the graphite in combination with washing, which is believed to convert water-insoluble metal impurities to water-soluble metal salts, such as metal hydroxides. Removal of metal salts in the graphite is accomplished by leaching in dilute sodium hydroxide solution and washing the purified graphite for further removal of water-soluble impurities.

[0003] The configurations herein are based in part on the observation that the increasing popularity of electric and hybrid vehicles (EVs and HVs) generates large volumes of used lithium-ion batteries containing charge materials such as NMC (Ni, Mn, Co) cathode materials and anode materials containing graphite and similar carbon forms. The regeneration process for NMC charge materials involves leaching of the used NMC charge materials, often with augmentation using a control (virgin) stock of Ni, Mn, Co salts to achieve a predetermined ratio of charge material metals according to technology or customer specifications. Graphite can also be recovered from used lithium-ion batteries. Unfortunately, conventional approaches to NMC regeneration have the drawback that the recovered graphite particles have impurities, most notably aluminum oxide, that remain as residues after the shredding and leaching process. If large amounts of impurities remain in the regenerated graphite product, meeting customer specifications for performance and physical anode material properties can be problematic. Thus, the compositions herein largely overcome the shortcomings of conventional battery reconditioning by producing anode materials containing graphite having improved purity of greater than 99.5% and approaching 99.9%.

[0004] More specifically, in a battery regeneration context to produce purified graphite for battery anode material, regeneration involves leaching the black mass of a depleted lithium-ion battery to obtain a leachate and precipitate. The leachate captures much of the cathode material, thereby leaving behind a residue as an undissolved precipitate that contains a large proportion of the graphite and / or other carbon forms used for the anode material. The two-phase roasting process involves a first sintering of the precipitate by preparing a slurry of the precipitate with a first aqueous solution of a hydroxide base having a hydroxide concentration of 40% by weight or less, and roasting the slurry of the precipitate at a temperature below 250° C. to form a sintered precipitate. Then, a further sintering of the sintered precipitate involves preparing a slurry of the sintered precipitate with a second aqueous solution of a hydroxide base having a hydroxide concentration of 40% by weight or less, and roasting the slurry of the sintered precipitate again at a temperature below 250° C. to form sintered graphite. Washing of the sintered graphite provides purified graphite for use as the anode charge material (anode material) in regenerative batteries.

[0005] BRIEF DESCRIPTION OF THE DRAWINGS These and other features will become apparent from the following description of specific embodiments disclosed herein, as illustrated in the accompanying drawings, in which like reference characters refer to the same parts throughout the different views. The drawings are not necessarily to scale, emphasis instead being placed upon illustrating the principles of the invention. [Brief description of the drawings]

[0006] [Figure 1] FIG. 2 is a context diagram of a playback environment suitable for use with the arrangements herein. [Diagram 2] 1 is a flow chart of the regeneration process disclosed herein. [Figure 3A] 1 is an example of the results of regenerated refined graphite. [Figure 3B] 1 is an example of the results of regenerated refined graphite. [Figure 3C]1 is an example of the results of regenerated refined graphite. [Figure 3D] 1 is an example of the results of regenerated refined graphite. [Figure 3E] 1 is an example of the results of regenerated refined graphite. [Figure 3F] 1 is an example of the results of regenerated refined graphite. [Figure 3G] 1 is an example of the results of regenerated refined graphite. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0007] Detailed Description Depicted below are exemplary methods and schemes for regenerating batteries, such as NMC batteries. The configurations herein utilize NMC battery chemistry as an example, but the disclosed schemes can be implemented with any suitable battery chemistry. Lithium-ion batteries utilize so-called battery chemistries that define the types and ratios of metal ions used to form the cathode material. The specific ratios are set by the manufacturer or recipient of the regenerated charge material. Suppliers of charge materials and charge material precursors produce charge material products that meet the specifications specified by the manufacturer. The anode material is almost always a carbon or graphite formulation, and the purity and morphology of the graphite are also set by the manufacturer.

[0008] FIG. 1 is a context diagram of a regeneration environment suitable for use with the configurations herein. With reference to FIG. 1, a regeneration scenario 100 begins with deployed lithium ion batteries 102, typically from an EV. Lithium ion batteries 102 have a finite number of charge cycles before the ability of the charge material to accept a sufficient charge is significantly degraded. In addition to this, there are batteries that have been terminated prematurely due to vehicle failure, crash damage, etc. The collective end-of-life regeneration stream contributes an abundant supply of depleted batteries including used cells and charge material 104. The batteries are discharged and agitated through pulverization, shredding, and grinding into a granular black mass. The leaching process receives the black mass including the charge material and any associated casings and copper and aluminum current collectors. The black mass including both the cathode material metal salt cathode material and the carbon and graphite anode material is used to form a leachate 106 of dissolved charge material metals.

[0009] The leachate is then separated from the graphite-rich precipitate to harvest the purified graphite, which is further described below, and the leachate follows a separate regeneration branch. For completeness, the leachate contains at least Ni, Mn, and Co in the sulfate solution from the sulfuric acid leach, although other charge material metals and / or leach acids may be utilized. The leachate 106 has a molar ratio of charge material metals (Ni, Mn, and Co) based on the constituent composition of the incoming regeneration stream. The molar ratio is adjusted with additional metal salts (Ni, Mn, and Co salts) such as sulfates (usually virgin or control forms of the fresh material) to provide a solution 108 adjusted to the target ratio.

[0010] A co-precipitation reaction occurs in one or more vessels 110 by adjusting the pH of the leachate to precipitate the charge material metals (charge materials) in the desired ratio resulting from the adjustment. Sodium hydroxide or another strong base causes the charge material metals, such as NMC, to come out of solution in a granular form that is typically separable by filtration as the hydroxide. The granular form co-precipitated from this leachate pH adjustment is the cathode material precursor with the desired molar ratio for the target battery chemistry for the new refurbished battery. Sintering in a furnace 112 with lithium carbonate or other lithium salt forms the active cathode material for the refurbished lithium ion battery. In an exemplary configuration, the active cathode material LiNi x Mn y Co z O2 is Ni x Mn y Co z The cathode material is synthesized by sintering (OH)2 and Li2CO3, where x, y, and z represent the respective molar ratios of Ni, Mn, and Co. Common chemical structures include NMC111, NMC811, NMC622, and NMC532, which represent equal molar contents of Ni, Mn, and Co, but any suitable molar ratio can be achieved by ratio adjustment and sintering in the leachate 106-108. The regenerated cathode material can then be merged back into the regeneration stream as cathode material, while the following process provides the anode material for the regenerated battery.

[0011] The remaining post-leaching precipitate provides a source of graphite, thereby supplementing the regeneration of the cathode material. Purification of graphite from exhausted lithium-ion batteries has been found to have the potential to provide anode high quality graphite material (>99.5%) for lithium-ion batteries. Purification of the graphite precipitate is achieved by repeated roasting processes that are believed to convert water-insoluble metal impurities to water-soluble metal hydroxides, followed by washing processes that are believed to remove these metal hydroxides in the graphite. An optional acid washing process can also be used to produce further purified regenerated graphite.

[0012] FIG. 2 is a flow chart 200 of the graphite regeneration process disclosed herein. With reference to FIGS. 1 and 2, leaching of the black mass in step 106 provides a leachate and a precipitate, the precipitate containing primarily solid unleached graphite from the battery anode as well as various impurities. The dissolved cathode material is leached and carried away with the leachate as disclosed in step 202. The undissolved precipitate contains a large percentage of graphite that is ideal for use as a regenerated anode material, typically having a purity of 82% to 97%, in combination with trace impurities. The precipitate may further contain ceramic impurities such as alumina, which is one of the most difficult impurities to remove from graphite.

[0013] The disclosed method of producing purified graphite from regenerated battery streams, which has been found to efficiently and effectively remove impurities, begins by sintering the precipitate as depicted in step 204. This involves preparing a slurry of the precipitate with a first aqueous solution of hydroxide base having a hydroxide concentration of 40% or less by weight, as depicted in step 206. The concentration of the first aqueous solution is preferably between 10% and 35% by weight, as depicted in step 208. Most preferred is a hydroxide base concentration of 20% to 30% by weight. In certain configurations, the hydroxide base is NaOH or KOH, as disclosed in step 210. However, any suitable hydroxide can be mixed with the precipitate. For example, the first aqueous solution of hydroxide base is a 7.5 M NaOH solution, which is combined with the precipitate during mixing. This combination forms a thick paste, which may have some resistance to mixing. However, preferably, a complete coverage of the graphite-containing precipitate is formed.

[0014] The precipitate slurry is then roasted at a temperature below 250° C. to form a sintered precipitate, as depicted in step 212. In some iterations, roasting at a temperature between 100° C. and 225° C., including temperatures between 120° C. and 180° C., may be sufficient, as depicted in step 214. The duration of the roasting may range from 1 to 20 hours, including 1 to 15 hours, as depicted in step 216. The roasting time may be adjusted relative to the roasting temperature, such that a higher temperature may receive a shorter time (faster roasting), while a lower temperature will benefit from a longer time (slower roasting). During roasting, it is preferred to mix or stir the roasted slurry, such as about every 40 minutes.

[0015] The mixing and roasting of the hydroxide slurry can be repeated until a predetermined number of iterations or a purity threshold is achieved, as depicted in step 218. In most cases, two roasting cycles have been found to be surprisingly efficient in forming battery grade graphite of at least 99% purity. For example, the sintered precipitate slurry resulting from the first iteration can be prepared with a second aqueous solution of hydroxide base having a hydroxide concentration of 40% by weight or less. The precipitate slurry is then roasted at a temperature less than 250° C. to form sintered graphite. Additional iterations can also be used. For each iteration, the concentration of the aqueous solution of hydroxide base and / or the type of base can be the same or different from the previous or subsequent iteration. The roasting times and temperatures used in each iteration can also be the same or vary from one another.

[0016] In general, the amount of aqueous hydroxide base solution can vary depending on the amount of graphite present. In an exemplary configuration involving two roasting iterations, the precipitate slurry has a ratio of precipitate to the first aqueous solution of about 1:1 to 1:4 (first iteration), and the sintered precipitate slurry is formed with a ratio of sintered precipitate to the second aqueous solution of about 1:1 to 1:4 (second iteration). Different ratios can also be used for each iteration.

[0017] Sintering is believed to form water-soluble hydroxides, most notably residual hydroxides of aluminum oxide. Thus, in a preferred embodiment, the sintered graphite is washed to form purified graphite, as depicted in step 220. The sintered graphite is typically washed with an aqueous wash solution to reduce the pH to approach 7, such as 6-10, including 6-8, as depicted in step 222. Washing includes suitable aqueous solutions including DI water and weak solutions of hydroxides, such as sodium hydroxide, having a lower concentration than the solution used for roasting. Straight water or an aqueous alkaline solution having a concentration of base that is 0.1M or less is also effective. In one particular example, a 0.1M NaOH solution is added to the sintered graphite, stirred for 30 minutes, and then filtered using vacuum filtration. The resulting washed graphite filter cake can be further washed by using water, particularly hot or boiling deionized water, with stirring, until the temperature is cooled to room temperature. The DI water wash can be repeated multiple times until a pH of about 7 is achieved. After the final wash and filtration, the filter cake can be dried, such as in a 140° C. convection oven overnight using drying sheets.

[0018] An improvement to the method includes, after washing the sintered graphite with the aqueous wash solution, a further wash with an acidic wash solution, as disclosed in step 224. The acidic wash solution may include HCl or sulfuric acid, as depicted in step 226. As an example of an HCL wash, 20 g of roasted graphite in a 500 mL glass beaker is combined with 20 mL of concentrated HCl (36.5%), and the combination is stirred for 1 hour to form a uniform dispersion. Alternatively, a relatively dilute acid concentration, such as a 9% or 18% HCl solution, may be used. The ratio of graphite to acid solution may be 1:1 to 1:4, such as 1:1 to 1:2, to achieve a final pH below neutral, such as less than 5 to 7. The washed dispersion is then filtered using vacuum filtration. Similar to the water / hydroxide wash described above, a filter cake form results to which boiling deionized water may be added with stirring until the temperature cools to room temperature. Multiple acid washes (three is an example) may be performed. After the final washing and filtration, the purified graphite filter cake was dried.

[0019] 3A-3C are exemplary characteristics of an exemplary purified graphite resulting from the disclosed method, including particle size distribution, tap density (TD, measured in gr / mL), and percent purity. The particle size distribution is generally represented by a number of values ​​that describe the shape of the distribution curve. In the figures, D10, D50, and D90 values ​​are recorded. D90 describes the particle size at which 90% of the particles have a relatively small particle size and 10% have a relatively large particle size. Similarly, D10 is the size at which 10% of the particles are relatively small and 90% are relatively large. D50 is the 50th percentile particle size within the distribution.

[0020] Referring to Figures 3A-3C, Figure 3A shows an analysis of the resulting purified graphite after a first roasting followed by a water wash. The purified graphite was found to have a purity of 98.63% and a particle size distribution (D50 of 15-25 microns) similar to commercial graphite. Figure 3B depicts the results after a double roasting (two iterations of sintering followed by a water wash) resulting in a similar particle size distribution and a significantly improved purity of 99.17%. In accordance with the claimed approach, the two roasting steps were found to produce graphite of relatively high purity.

[0021] Finally, Figure 3C shows three trials corresponding to the resulting purified graphite products from different preferred embodiments of the disclosed method. In these figures, as can be observed in column 1, the control group, which is the precipitate recovered after leaching of black mass and subsequent washing with DI water, results in a purity of about 97%. In the second column, two roasting cycles similar to that in Figure 2 using 7.5 M NaOH solution for each roasting step and subsequent washing of the resulting purified graphite with DI water after double roasting produces a purified graphite product having a purity of 98.92%, which is a significant improvement over the control washed graphite. Furthermore, as shown in the third column, the inclusion of a further wash with 37% HCl solution (1:1) followed by a final water wash shows an exemplary purity of 99.90% in the purified graphite product.

[0022] 3D and 3E show properties of further examples of purified graphite products of the present disclosure. As shown in FIG. 3D, two examples of purified graphite were prepared by using a double roasting process with 7.5 M NaOH solution for each roasting step followed by washing with dilute aqueous base (0.1 M NaOH solution) to a pH of 9-10 and DI water. Sample 1 was prepared by roasting at a temperature of 150° C. for 4 and 8 hours, while Sample 2 was prepared by roasting at a temperature of 120° C. for 8 and 10 hours. After washing, Sample 1 was found to have a high purity value of 99.29%, and Sample 2 had a relatively high purity of 99.61%. In addition, the inclusion of an HCl / water wash provided further improved purity values ​​of 99.76% and 99.81%, respectively. This demonstrates that relatively low roasting temperatures for slightly longer times can be used to produce purified graphite products with significantly higher purity values. FIG. 3E shows the particle size distribution of Sample 2 along with acceptable tap density values, which are consistent with those shown in FIGS. 3A-3C.

[0023] In addition, Figures 3F and 3G show properties of further examples of purified graphite products of the present disclosure. As shown in Figure 3F, two samples of purified graphite were prepared by using a double roasting process with 7.5 M NaOH for each roasting step, followed by washing with dilute aqueous base (0.1 M NaOH solution) to a pH below 8 and DI water. Sample 3 was prepared by two roasts at a temperature of 200°C for 4 hours, and Sample 4 was prepared by two roasts at a temperature of 150°C for 8 hours. After washing, Sample 3 and Sample 4 were found to have purity values ​​of 99.24% and 99.23%, respectively. In addition, the inclusion of an HCl / water wash provided further improved purity of 99.99% and 99.90%, respectively. Figure 3G shows the particle size distribution of Samples 3 and 4 along with acceptable tap density values, which are consistent with those shown in Figures 3A-3C and 3E.

[0024] While the systems and methods defined herein have been particularly illustrated and described above with reference to embodiments thereof, those skilled in the art will understand that various changes in form and details may be made therein without departing from the scope of the invention as encompassed by the appended claims. [Explanation of symbols]

[0025] 100 Playback Scenarios 102 Lithium-ion battery 104 Used cells and charge materials 106 Exudate 108 Exudate 110 Container 112 Furnace 200 Flowchart 202 Steps 204 Steps 206 Steps 208 Steps 210 Steps 212 Steps 214 Steps 216 Steps 218 Steps 220 Steps 222 Steps 224 Steps 226 Steps

Claims

1. 1. A method for producing purified graphite from a regenerated battery stream, comprising: leaching the black mass of a depleted lithium ion battery to obtain a leachate and a precipitate comprising graphite; The precipitate is subjected to preparing a slurry of the precipitate with a first aqueous solution of a hydroxide base having a hydroxide concentration of 40% by weight or less; and roasting the slurry of the precipitate at a temperature less than 250° C. to form a sintered precipitate. and sintering the mixture by The sintered precipitate is subjected to preparing a slurry of the sintered precipitate with a second aqueous solution of a hydroxide base having a hydroxide concentration of 40 wt.% or less; and roasting the slurry of sintered precipitate at a temperature less than 250° C. to form sintered graphite. and sintering the mixture by washing the sintered graphite to form purified graphite. The method includes:

2. 10. The method of claim 1, wherein the slurry of the precipitate is prepared at a ratio of the precipitate to the first aqueous solution of about 1:1 to 1:

4.

3. 2. The method of claim 1, wherein the slurry of the sintered precipitate is prepared at a ratio of the sintered precipitate to the second aqueous solution of about 1:1 to 1:

4.

4. The method of claim 1 , wherein the concentration of the first aqueous solution and the concentration of the second aqueous solution are the same.

5. 2. The method of claim 1, wherein the concentration of the first aqueous solution, the concentration of the second aqueous solution, or both is between 10% and 35% by weight.

6. 2. The method of claim 1, wherein the concentration of the first aqueous solution, the concentration of the second aqueous solution, or both is between 20% and 30% by weight.

7. 2. The method of claim 1, wherein the hydroxide base is NaOH or KOH.

8. 2. The method of claim 1, wherein the slurry of the precipitate, the slurry of the sintered precipitate, or both are roasted at a temperature of from 100°C to 225°C.

9. 2. The method of claim 1, wherein the slurry of the precipitate, the slurry of the sintered precipitate, or both, are roasted for a time period of from 1 to 20 hours.

10. The method of claim 9, wherein the time is from 1 to 15 hours.

11. The method of claim 1 , wherein the precipitate further comprises ceramic impurities.

12. The method of claim 11 , wherein the ceramic impurity is alumina.

13. 2. The method of claim 1, wherein the sintered graphite is washed with an aqueous wash solution to a pH of 6 to 10.

14. The method of claim 13 , wherein the aqueous cleaning solution is water.

15. 14. The method of claim 13, wherein the aqueous wash solution is an alkaline aqueous solution having a concentration of base of 0.1 M or less.

16. 14. The method of claim 13, further comprising, after washing the sintered graphite with the aqueous washing solution, further washing with an acidic washing solution, followed by washing with water.

17. The method of claim 16 , wherein the acidic cleaning solution comprises HCl or sulfuric acid.

18. The method of claim 1 , wherein the precipitate comprises graphite having a purity of between 82% and 97%.

19. 10. The method of claim 1, wherein the purified graphite has a purity of greater than 99.5%.

20. 1. A method for producing purified graphite from a regenerated battery stream, comprising: leaching the black mass of a depleted lithium ion battery to obtain a leachate and a precipitate containing ceramic impurities including graphite and alumina having a purity of 82% to 97%; The precipitate is subjected to preparing a slurry of the precipitate using an aqueous NaOH solution having a hydroxide concentration of 20% to 30% by weight; and Roasting the slurry of the precipitate at a temperature of 150° C. to 220° C. to form a sintered precipitate. and sintering the mixture by The sintered precipitate is subjected to preparing a slurry of the sintered precipitate using the aqueous NaOH solution; and roasting the slurry of sintered precipitate at a temperature of 150°C to 220°C to form sintered graphite. and sintering the mixture by washing the sintered graphite with an aqueous wash solution to form purified graphite having a purity of greater than 99.5%. The method includes:

Citation Information

Patent Citations

  • Recycling method of battery

    JP2006331707A

  • Method of recovering positive electrode active material from lithium battery, and reuse thereof

    JP2010062105A

  • Method for collecting and reusing negative electrode active material of lithium ion battery

    JP2014127417A

  • Method of peeling carbon from copper foil surface of negative electrode sheet of lithium ion battery and peeling agent for use in the same

    JP2015026566A